Comprehensive analysis of NAC transcription factor family uncovers drought and salinity stress response in pearl millet (Pennisetum glaucum) - Ambika Dudhate; Harshraj Shinde; Pei Yu; Daisuke Tsugama; Shashi Kumar Gupta; Shenkui Liu; Tetsuo Takano (BMC Genomics, 2021)
Abstract Background Pearl millet (Pennisetum glaucum) is a cereal crop that possesses the ability to withstand drought, salinity and high temperature stresses. The NAC [NAM (No Apical Meristem), ATAF1 (Arabidopsis thaliana Activation Factor 1), and CUC2 (Cup-shaped Cotyledon)] transcription factor family is one of the largest transcription factor families in plants. NAC family members are known to regulate plant growth and abiotic stress response. Currently, no reports are available on the functions of the NAC family in pearl millet. Results Our genome-wide analysis found 151 NAC transcription factor genes (PgNACs) in the pearl millet genome. Thirty-eight and 76 PgNACs were found to be segmental and dispersed duplicated respectively. Phylogenetic analysis divided these NAC transcription factors into 11 groups (A-K). Three PgNACs (− 073, − 29, and − 151) were found to be membrane-associated transcription factors. Seventeen other conserved motifs were found in PgNACs. Based on the similarity of PgNACs to NAC proteins in other species, the functions of PgNACs were predicted. In total, 88 microRNA target sites were predicted in 59 PgNACs. A previously performed transcriptome analysis suggests that the expression of 30 and 42 PgNACs are affected by salinity stress and drought stress, respectively. The expression of 36 randomly selected PgNACs were examined by quantitative reverse transcription-PCR. Many of these genes showed diverse salt- and drought-responsive expression patterns in roots and leaves. These results confirm that PgNACs are potentially involved in regulating abiotic stress tolerance in pearl millet. Conclusion The pearl millet genome contains 151 NAC transcription factor genes that can be classified into 11 groups. Many of these genes are either upregulated or downregulated by either salinity or drought stress and may therefore contribute to establishing stress tolerance in pearl millet.